The short ionizing photon mean free path at z = 6 in Cosmic Dawn III: a new fully coupled radiation-hydrodynamical simulation of the epoch of reionization - Lewis, Joseph; Ocvirk, Pierre; Sorce, Jenny G; Dubois, Yohan; Aubert, Dominique; Conaboy, Luke; Shapiro, Paul R; Dawoodbhoy, Taha; Teyssier, Romain; Yepes, Gustavo; Gottlöber, Stefan; Rasera, Yann; et al. (Monthly notices of the Royal Astronomical Society, 2022)
RRecent determinations of the mean free path of ionizing photons (mfp) in the intergalactic medium (IGM) at z = 6 are lower than many theoretical predictions. In order to gain insight, we investigate the evolution of the mfp in our new massive fully coupled radiation-hydrodynamics cosmological simulation of reionization: Cosmic Dawn III (CoDa III). CoDa III’s scale (943 cMpc3) and resolution (81923 grid) make it particularly suitable to study the IGM during reionization. ...